Analysis of MSME Growth in East Kalimantan - Indrayani; Tri Wahyu Hardaningrum; Tiara Alifia (Jurnal Penelitian Ekonomi dan Akuntansi (JPENSI), 2023)
MSME and Cooperative Assistants play an important and strategic role in supporting the success of the MSME and Cooperative programs, especially in the economic business of MSME and Cooperative actors so that the potential that exists in the community can be optimally empowered and developed. Good and professional assistance will have a positive impact on the local economy in particular and at the same time the national economy. The MSME and Cooperative Assistant is expected to be a reference in carrying out tasks and coordinating with relevant agencies in supporting the success of the MSME and Cooperative assistance program. Various efforts in the context of MSME development have been carried out by various parties, including by introducing approaches in the framework of MSME financing such as the PHBK pattern, the cluster approach pattern, and the partnership pattern. Lastly, the approach taken by the Government is to optimize the use of BDSP personnel who can function as a bridge between MSMEs and banks. It is believed that the use of BDSP personnel can also assist the government in the success of the poverty alleviation program by optimizing bank lending to MSMEs